Determination of the Level of some Adipokines in Hypo-and Hyperthyroids Patients in Baghdad City (Baghdad Science Journal, 2025)
Determination of the level of adipokines (obestatin, vaspin, tumor necrosis factor-? and interleukin-6)in hypo-and hyperthyroid patients from Educational Baghdad Hospital in Baghdad City was investigated. Fifty patients with hypothyroidism and Fifty patients with hyperthyroidism were selected. A control group of thirty euthyroid persons was included. Blood was collected by vein puncture and serum was separated and stored at –20C. Adipokines (obestatin, vaspin, tumor necrosis factor-? and interleukin-6) were estimated using ELISA method. The findings show a significant (p